Reliability of the calculated maximal lactate steady state in amateur cyclists - Adam, Jennifer; Oehmichen, Matthias; Oehmichen, Eva; Rother, Janine; Müller, Ulrike Maria; Hauser, Thomas; Schulz, Henry (Biology of Sport, 2015)
Complex performance diagnostics in sports medicine should contain maximal aerobic and maximal anaerobic performance. The requirements on appropriate stress protocols are high. To validate a test protocol quality criteria like objectivity and reliability are necessary. Therefore, the present study was performed in intention to analyze the reliability of maximal lactate production rate ( VLamax) by using a sprint test, maximum oxygen consumption ( VO 2max ) by using a ramp test and, based on these data, resulting power in calculated maximum lactate-steady-state (PMLSS) especially for amateur cyclists. All subjects (n=23, age 26 ± 4 years) were leisure cyclists. At three different days they completed first a sprint test to approximate VLamax. After 60 min of recreation time a ramp test to assess VO 2max was performed. The results of VLamax-test and VO 2max -test and the body weight were used to calculate PMLSS for all subjects. The intra class correlation (ICC) for VLamax and VO 2max was 0.904 and 0.987, respectively, coefficient of variation (CV) was 6.3 % and 2.1 %, respectively. Between the measurements the reliable change index of 0.11 mmol∙l-1∙s-1 for VLamax and 3.3 ml∙kg-1∙min-1 for VO 2max achieved significance. The mean of the calculated PMLSS was 237 ± 72 W with an RCI of 9 W and reached with ICC = 0.985 a very high reliability. Both metabolic performance tests and the calculated PMLSS are reliable for leisure cyclists.